Induction of mucosal and systemic immune responses against the common O78 antigen of an oral inactivated ETEC vaccine in Bangladeshi children and infants. Issue 2 (21st January 2022) - Svennerholm, Ann-Mari; Qadri, Firdausi; Lundgren, Anna; Kaim, Joanna; Rahman Bhuiyan, Taufiqur; Akhtar, Marjahan; Maier, Nicole; Louis Bourgeois, A.; Walker, Richard I.
Abstract: We tested an oral enterotoxigenic Escherichia coli (ETEC) vaccine, ETVAX, consisting of inactivated E. coli overexpressing the most prevalent ETEC colonization factors (CFs) and a toxoid (LCTB A), in Bangladeshi children for capacity to induce mucosal and plasma immune responses against O78 lipopolysaccharide (LPS) expressed on the vaccine strains. The vaccine was given ± double-mutant heat-labile toxin (dmLT) adjuvant. We evaluated the impact of dmLT on anti-O78 LPS immune responses and whether such responses can predict responses against the CFs as a marker for vaccine "take". Two fractionated doses of ETVAX ± different amounts of dmLT were administered biweekly to groups of children 24–59 (n = 125), 12–23 (n = 97) and 6–11 (n = 158) months of age. Immune responses were evaluated in antibody in lymphocyte supernatants (ALS), fecal extracts and plasma. ALS IgA responses against O78 LPS were induced in 44–49% of the children aged 12–59 months. The magnitudes of the ALS responses were significantly higher in children receiving a half-dose (5 × 10 10 bacteria) of ETVAX ± dmLT than in placebo recipients. <10% of the vaccinees aged 6–11 months mounted ALS responses against O78 LPS. However, 49% of the infants developed fecal secretory IgA responses which were significantly more frequent in those receiving a quarter-dose (2.5 × 10 10 bacteria) of vaccine + dmLT (62%) compared to a quarter-dose alone (36%). Plasma IgA antibody responses were induced in 80% of older children and 36% of infants. The frequencies of O78 LPS responses in plasma and feces were comparable or higher than against the vaccine CFs in infants. Our findings show that ETVAX induced mucosal and systemic immune responses against O78 LPS in all age groups and that dmLT improved intestinal immune responses among infants. These observations may have implications for more successful use of other oral vaccines based on O antigens in children.